(untitled) - Lynne Reid Banks (Avon Camelot, 1980)
"The Indian in the Cupboard" by Lynne Reid Banks tells the enchanting story of a young boy named Omri who discovers a magical cupboard that can bring his toys to life. When he places a plastic Indian figurine inside, the toy becomes a real, living being named Little Bear.
Keywords: Children's literature; Fantasy